2014
DOI: 10.1159/000362787
|View full text |Cite
|
Sign up to set email alerts
|

Bazex Syndrome Revealing a Gastric Cancer

Abstract: We herein report the case of a 73-year-old woman who developed skin and nail disorders 2 months before her digestive symptoms started, which lead to the diagnosis of gastric adenocarcinoma. The lesions were diagnosed as Bazex syndrome, usually seen in squamous cell carcinoma. Under systemic chemotherapy, the cutaneous signs improved for some months before worsening when the disease progressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…[6] We found Bazex syndrome in two patients with primary tumor of stomach and colon, this association has also been reported in the literature. [17][18] Skin lesions of Bazex usually precede the diagnosis of primary tumor in 65-70%, follow the diagnosis in 10-15% and have concurrent onset in 15-25% of cases. [19] In our study one (50%) patient developed skin lesions seven months prior to the diagnosis of adenocarcinoma stomach, while another patient (50%) had concurrent onset.…”
Section: Discussionmentioning
confidence: 99%
“…[6] We found Bazex syndrome in two patients with primary tumor of stomach and colon, this association has also been reported in the literature. [17][18] Skin lesions of Bazex usually precede the diagnosis of primary tumor in 65-70%, follow the diagnosis in 10-15% and have concurrent onset in 15-25% of cases. [19] In our study one (50%) patient developed skin lesions seven months prior to the diagnosis of adenocarcinoma stomach, while another patient (50%) had concurrent onset.…”
Section: Discussionmentioning
confidence: 99%
“…Bolognia et al [ 2 ] reported that 16% of such patients developed vesicles, bullae, and crusts, in addition to psoriasiform hyperkeratosis. Additionally, Robert et al [ 5 ] reported a patient with Bazex syndrome who developed ascites, but the association was not described.…”
Section: Discussionmentioning
confidence: 99%
“…But we also found some cases of gastric cancer who hasn't had any of these common symptoms of gastric cancer. Those non-specific manifestations or paraneoplastic presentation were varied a lot in gastric cancer, including dermatitis [1,2], polyarthritis [3], neuropathy [4], or kidney problems and so on. Doctors should pay more attention to those patients who couldn't get any effect from the treatments to their initial manifestations.…”
Section: Introductionmentioning
confidence: 99%